Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1002/ajh.1174
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors increase p21WAF1 and induce apoptosis of human myeloma cell lines independent of decreased IL‐6 receptor expression

Abstract: Histone deacetylase (HDAC) inhibitors cause growth arrest and apoptosis of cancer cells by both p21-dependent and independent mechanisms. Decreased expression of growth factor receptors may be a key factor in the p21-independent mechanism, although this has not been directly tested. We have tested the effects of sodium butyrate and trichostatin A on human myeloma cell lines and have observed G1 arrest and apoptosis associated with increased expression of p21(WAF1), Bax, Rb dephosphorylation, and decreased IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 23 publications
2
57
0
Order By: Relevance
“…In the group of genes that was found to be down-regulated in the liver of HBxtransgenic mice, we observed several genes like SAA3, aldolase A, creatine kinase, phospholipase A2 that have been reported elsewhere as up-regulated during the course of liver regeneration [22][23][24] . Interestingly, down-regulation of histone deacetylase and up-regulation of DNA repair genes (Rad52 and MSH6) observed in our study in HBx-transgenic mice after PH have, in agreement with other reports, similar effect on the cell cycle by inducing cell cycle arrest [25][26][27][28] . Furthermore, it has previously been reported that HBx expression may interfere with nucleotide excision repair mechanisms [29,30] and interact with the DNA repair protein [31,32] .…”
Section: Microarray Analysis Of Gene Expression In the Liver Of Hbx-tsupporting
confidence: 80%
See 1 more Smart Citation
“…In the group of genes that was found to be down-regulated in the liver of HBxtransgenic mice, we observed several genes like SAA3, aldolase A, creatine kinase, phospholipase A2 that have been reported elsewhere as up-regulated during the course of liver regeneration [22][23][24] . Interestingly, down-regulation of histone deacetylase and up-regulation of DNA repair genes (Rad52 and MSH6) observed in our study in HBx-transgenic mice after PH have, in agreement with other reports, similar effect on the cell cycle by inducing cell cycle arrest [25][26][27][28] . Furthermore, it has previously been reported that HBx expression may interfere with nucleotide excision repair mechanisms [29,30] and interact with the DNA repair protein [31,32] .…”
Section: Microarray Analysis Of Gene Expression In the Liver Of Hbx-tsupporting
confidence: 80%
“…In this context, we showed that HBx down-regulated HDAC10 and up-regulated DNA repair gene (Rad52 and MSH6) expression, which may have a similar impact on the cell cycle. Indeed, HDAC inhibition causes cell cycle arrest due to an increase in the expression of p21 WAF1/Cip1 and Rb [25,26,41,42] . Moreover, it has been reported that Rad52 over-expression affects cell cycle regulation by delaying the exit from G1 [27] , and that MSH6 protein induces apoptosis by activation of p53 [28] .…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous reports that DNA demethylation is not required for p21 induction but results from treatment with a histone deacetylase inhibitor. 33 In addition, reduction of DNMTase level by antisense oligonucleotides could increase p21 protein independently of the methylation status of p21/ CDKN1A in cancer cell lines. 34,35 The lack of p21 promoter methylation led us to postulate p73 as a target of 5-Aza-CdR-mediated demethylation in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HDAC inhibitors trigger cell cycle arrest, apoptosis, autophagy, differentiation and also inhibit metastasis and angiogenesis of cancerous cells through multiple mechanisms [60]. HDAC inhibitors alter the levels of cell cycle regulatory proteins such as p21 WAF1/CIP1 and p27 KIP1 and cause Rb hyperphosphorylation [61][62][63][64][65][66][67]. They actually trigger cell apoptosis by inducing proapoptotic members such as Bax, Bak, Nova, Bim and Puma and also by decreasing the expression of anti-apoptotic proteins such as Bcl-2, Bcl-X L and Mcl-1 [68][69][70][71][72].…”
Section: (De)acetylation and Cancermentioning
confidence: 99%